탄광부 진폐증 환자에서 맞춤형 호흡 재활 치료 프로그램의 임상적 효용성 - 정희; Hee Cheong; 이정민; Jeong Min Lee; 박인기; In Ki park; 김종규; Jong Kyu Kim; 전근재; Geun Jae Jeon; 김주령; Ju Ryung Kim; et al. (The Korean journal of medicine, 2014)
목적: 두 개의 병원에 입원 중인 진폐증 환자 가운데 53명을 대상으로 호흡 재활 치료 프로그램을 12주 동안 시행하여 임상적 효과를 분석하였다. 방법: 환자 개개인의 운동 능력에 따라 운동 속도와 부하 중량을 차등화한 호흡 재활 치료 프로그램으로 트레드밀을 이용한 지구력 운동과 에르고미터를 이용한 상하지 근력 운동을 매주 3회 시행하였다. 프로그램을 시행한 전후 폐 기능 검사, 6분 보행 거리, 상하지 근력, 중간 허벅지 둘레 길이 및 SGRQ를 측정하였다. 결과: 환자의 평균 나이는 66.8 ± 6.6세였으며, 13명이 도중에 탈락하였다. 프로그램 치료 전후 대상 환자의 주관적인 호흡곤란(modified Borg’s scale)은 평균 3.52점 감소하였으며 (p < 0.0001), 6분 보행 거리는 평균 45.18 m 증가하였다. 중간 허벅지 둘레 길이는 평균 0.83 cm 증가하였으며(p < 0.0001), 일정 부하 중량에 대한 상하지 근력 운동 횟수는 각각 9.98 회 및 8.90회 증가하였다(p < 0.0001). 삶의 질에 있어서도 SGRQ는 평균 10.7점이 개선되었다(p = 0.007). FEV1.0 < 60%인 환자들에서도 호흡곤란 증상의 개선 및 운동 능력과 삶의 질의 유의한 향상을 관찰할 수 있었다. 호흡 재활 치료 프로그램과 함께 금연을 시행한 환자에서는 흡연을 지속한 환자에 비해 6분 보행 거리(p < 0.0001)와 삶의 질 향상(p = 0.002)을 더욱 기대할 수 있으며, FEV1.0 둔화 감소(p = 0.031) 와 PEFR의 개선 효과(p = 0.017)도 얻을 수 있다. 호흡 재활치료 프로그램에서 탈락된 주된 이유는 운동 중 어지러움과 관절통이었으며, 초기(평균 2.3 ± 1.7주)에 탈락하는 경향을 보였다. 결론: 저자들은 진폐증 환자를 대상으로 맞춤형 호흡 치료 프로그램을 시행하여 운동 능력 및 삶의 질을 향상시킬 수 있으며, 금연을 병행할 경우 개선 효과를 더욱 높일 수 있음을 보고하는 바이다. Background/Aims: It is unknown whether pulmonary rehabilitation (PR) is an effective intervention to manage coal worker pneumoconiosis (CWP). We evaluated the efficacy and safety of an individualized PR program in 53 patients with CWP hospitalized in two medical institutions. Methods: The PR program consisted of upper and lower extremity exercises to improve exercise endurance and skeletal musculoskeletal strength. All subjects performed treadmill and ergometer exercise with steady loading weights three times/week for 12 weeks. The following tests were performed before and after the study to investigate the efficacy of the PR program: modified Borg scale, pulmonary function test, mid-thigh circumference, maximum muscular strength, 6-min walk distance (6MWD), and the St. George’s Respiratory Questionnaire (SGRQ), Korean version. Results: Forty patients (75.5%) completed their PR programs. They improved significantly on the modified Borg scale, mid thigh circumference, maximum muscular strength, 6MWD (all p < 0.000), and SGRQ (p = 0.007), however, no significant improvement was observed on the pulmonary function test. A significant improvement in dyspnea (p = 0.004) and 6MWD (p = 0.002) was observed in 12 patients with forced expiratory volume in 1 sec < 60%. The PR program with smoking cessation resulted in significantly more improvement on the 6MWD (p < 0.0001) and the SGRQ score (p = 0.002), as compared to those of patients who did not quit smoking. Conclusions: Our results show that an individualized 12-week PR program improves exercise capacity and quality of life for patients with CWP. (Korean J Med 2014,87:690-697)